How do fund rates affect the U.S. firms? A threshold estimation - Mina Sami; Tarek Ibrahim Eldomiaty; Mina Kamal (Central Bank Review (CBR), 2020)
Purpose The financing of growth of the firm is quite sensitive to fluctuations in Fund rates. This requires a treatment of Fund rates being subject to structural shifts. This paper examines the impact of threshold Federal Fund Rate (FFR), being a proxy for Federal Reserve policy, on different dimensions of growth of the US firm. The goal is to examine the extent to which shifts in FFR cause changes in firms' growth using three main proxies: assets, sales revenue and number of employees. Design/methodology/approach This paper follows "Threshold Fixed Effect" model as a new methodological treatment that offers a structural change in the sources of funds for financing growth of the firms. The authors propose that "Threshold Fixed effect regression" and "Threshold First Difference Generalized Method of Moments" provide robust results of the impact of FFR shifts on growth of the firms. Findings The main findings are as follows. First, the impact of FFR is substantially significant on growth of the firms listed in S&P500 when FFR declines below the threshold point 1.35 percent. That is, a slight move in the FFR adversely affects growth of firms four times higher relative to the situation when FFR is greater than 1.35 percent. Second, as far as actual Fund rates are fluctuating around zero percent, the results show that each one percent increase in the FFR is associated with a decrease in the firm size by 0.5 percent. Originality/value This paper offers three significant contributions to the literature. First, this paper offers a novel treatment of the effect of Fund rates on the financing of growth of the firm. As far as the authors' knowledge is concerned, this paper might be the first attempt to use "Threshold fixed effect" model to estimate the effects of threshold FFR on growth of the firm. Second, the results of threshold FFR offer robust evidence that theories of firm capital structure are contingent on structural changes in threshold interest rates. Third, this paper provides an empirical guidline to central banks regrading the determination of Fund rates that help firms to grow.
Keywords: D22; D25; F23; L25; 330; Corporate growth; Federal fund rate; Threshold fixed effect; Sales revenue; Assets; Employees; S&P500